Attitudes Towards Police and Weapon Carriage Among Adolescents - Cunningham, Mary C. (American journal of criminal justice, 2022)
While much is known about attitudes towards police and weapon carriage independently, it is unclear whether the two are associated. In the current study, we explored this potential association and whether it was moderated by race in a sample of adolescents. After adjusting for age, gender, perceived risk of victimization, and violence victimization, logistic regression models indicated that more positive attitudes toward police were associated with lower weapon carriage. In particular, among Black youth, the association between attitudes toward police and weapon carriage was larger than non-Black youth. Our results suggest that race plays an important role in this association. Efforts to build positive community-police relationships may be an effective strategy for reducing weapon carriage and ultimately, injury and fatality.